Serodetection of viruses associated to barley yellow dwarf (BYD) on cereals in Algeria - Belkahla, H.; Lapierre, H. (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ)l, 1999)
Surveys on viruses associated with Barley Yellow Dwarf (BYD) and their vectors were carried out in Algerian cereal areas (Guelma, Constantine, Algiers, Sidi-belabes, Adrar) in 1997 and 1998. Rhopalosiphum padi was present in all zones of culture, whereas R. maidis, Sitobion avenae, S. fragariae and Schizaphis graminum had only local distributions. In most areas BYD-like symptoms, i.e. dwarfing and yellowing of barley (Hordeum vulgare), dwarfing and reddening of oat (Avena sativa) and wheat (Triticum aestivum), were observed. Serological tests were done on these crops using DAS-ELISA (RMV and SGV) or TAS-ELISA using monoclonal antibodies specifie to CYDV-RPV or using different variant specifie BYDV-PAV (CpA and CpB) and BYDV-MAV monoclonal antibodies. BYDV-PAV was prevalent and few plant samples carrying RMV, SGV, BYDV-MAV or CYDV-RPV were detected. The relative frequencies of BYDV-PAV CpA and CpB serotypes were variable depending on the area and the crop season. The range of symptoms induced on barley by both Algerian BYDV-PAV CpB and BYDV-PAV CpA serotypes was mild to severe. Twenty-one BYDV-MAV isolates were compared using monoclonal antibodies, which distinguish two serotypes of this virus. Only one serotype was detected. This same serotype is also the most prevalent in Europe.